The value of Virginia Woolf - Detloff, Madelyn
"One cannot speak of value without implicitly or explicitly speaking of values. Barbara Herrnstein Smith made this point eloquently clear in her meticulous study of the "double discourse" of value, Contingencies of Value. "On the one hand," Smith explains, "there is the discourse of economic theory: money, commerce, technology, industry, production and consumption, workers and consumers; on the other hand, there is the discourse of aesthetic axiology: culture, art, genius, creation and appreciation, artists and connoisseurs." These two "hands" may use different yardsticks for measuring what is worth one's time, money, effort, or attention, but both participate in the same complex, dynamic system of evaluation-a system that is social and interdependent, rather than presocial or transcendent. Arguing that "All value is radically contingent, being neither a fixed attribute, an inherent quality, or an objective property of things but, rather, an effect of multiple, continuously changing, and continuously interacting variables," Smith eschews the notion of intrinsic aesthetic value (a value that inheres in things, in works), and claims rather that value is conferred through communal processes-that is, through the work of valuing"--